Ovarıan Teratoma In Pedıatrıc Populatıon: Our Clınıcal Experıence Of Seven Years - Burhan Beger; Erbil Karaman; Baran Serdar Kızılyıldız; Metin Şimşek; Ebuzer Düz (Van Tıp Dergisi, 2020)
INTRODUCTION: In relation to torsion, mass appearance may occur due to hemorrhage into the cyst, and blood supply of the over tissue may not be well evaluated radiologically. For this reason, the diagnosis of torsion and non-torsion MCT continues to be a serious dilemma. METHODS: The laboratory and imaging methods of ovarian teratomas with or without torsion were compared with the statistical method. The results were evaluated statistically by using SPSS version 24. Normality checks were performed with the Shapiro-Wilk test. The groups were compared with the independent samples t-test. Statistical significance was p <0.05. RESULTS: 40% of the cases with CRP level elevation, torsion were significantly higher (> 5 mg / L). The most common surgical approach was fertilization protective cystectomy applied in 14 cases (77 %). DISCUSSION AND CONCLUSION: The first choice in benign ovarian masses is fertility protective surgery. CRP, WBC and CA19-9 can be a marker, especially in torsion cases. The planning of the study with prospective and large number of patients will be appropriate.